“Revive, Sisters!”: Chinese women in ministry through the lens of the Canaan Hymns - Yang, Xiaoli (Missiology, 2025)
“Half of the Sky”, a phrase used to describe the rise of women in the New China of the 1960s, can equally apply to the tremendous legacy of Chinese women in Christian ministry in the contemporary indigenous movement. This paper amplifies the voices of Chinese women in ministry and studies the feminine motif in the song collection known as Canaan Hymns. Drawing from the methodologies of lived theology through textual analysis, interviews, and literature reviews, firstly it examines some biblical portraits of women resonating with the experiences of female Chinese itinerants; secondly the embodied spirit-filled experiences coupled with feminine tenderness and flaming passion; lastly the organic ecclesiology that empowers female leadership. It is argued that the hymns offer a unique poetic window into the lived experiences of Christian women, providing nuances and complexity of gender, identity, body, spirituality and relationality in the recent history of Chinese Christianity.